Les Portugais dans l’Empire du Brésil (1822-1889) : les trajectoires spécifiques des hommes de lettres au sein de la colonie portugaise de Rio de Janeiro - Sébastien Rozeaux (Confins)
The almost constant growth of the Portuguese entries in Second half of the 19th century Rio de Janeiro straightens the foundations of a Portuguese colony in the Empire Capital. Active in both the economic and commercial businesses, this colony also promotes social networks in the domains of charity, sport and culture in order to help the colony’s members and protect their own interests. More specifically, the men of letters who create the few literary Portuguese associations in Rio de Janeiro try to defend the Kingdom’s greatness, to fight against lusofobia through the promotion of the Luso-Brazilian Fraternity paradigm and to facilitate their own inclusion in the carioca public space.